Current Potential Options for COVID-19 Treatment in Iraq- Kurdistan Region and the Rest of the World: A Mini-review - Faraj, Aryan M.; Qadir, Syamand A.; Mohammed, Othman A.; Aziz, Peshawa Y.; Alkhafaji, Marwa; Rahman, Heshu S.; Abdul Aziz, Jeza M.; Othman, Hemn H.; Mohan Adai AL-Zubaidy, Adel (Iraqi Journal of Science, 2022)
COVID-19 is an infectious pandemic disease which is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Up to date, scientists are trying to identify a new specific antiviral drug to overcome this disease. Different methods are under study and evaluation in the entire world to control the virus, including blood plasma, blood purification, and antimicrobial and antiviral agents; however, there are no approved drugs yet. This review is focused on the conducted clinical trials worldwide, including the Iraq- Kurdistan region, China, USA, and Europe, to find relevant data on the agents with potential efficacy to treat the COVID-19 infection. The utmost commonly assessed therapies for this disease were chloroquine phosphate, hydroxyl-chloroquine, azithromycin, lopinavir/ritonavir, favipiravir, remdesivir, and alternatively, blood plasma, ivermectin in combination with doxycycline, and dexamethazone. This review suggests that blood plasma transfusion, the combination of hydroxyl-chloroquine with azithromycin, and remdesivir were the most abundant and efficient therapies. Thus, more light could be shed on these particular drugs on the road of drug investigation against COVID-19 pneumonia.